Dukungan yang Diperlukan Oleh Wanita Untuk Meniti serta Menjalani Karir - Widjayanti, Arifiani (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2009)
Career for a woman is something that it is more difficult to do than career for a man, as long as it is not expected to do by a woma. A woman decides to do career because of many things. There are influences of family, supports from family, support from outside, dependences of money, challenges, and intelelectual interest.